S100B alters neuronal survival and dendrite extension via RAGE-mediated NF-κB signaling - Villarreal, Alejandro (2011)
S100B is a soluble protein secreted by astrocytes that exerts pro-survival or pro-apoptotic effects depending on the concentration reached in the extracellular millieu. The S100B receptor termed RAGE (for receptor for advanced end glycation products) is highly expressed in the developing brain but is undetectable in normal adult brain. In this study, we show that RAGE expression is induced in cortical neurons of the ischemic penumbra. Increased RAGE expression was also observed in primary cortical neurons exposed to excitotoxic glutamate (EG). S100B exerts effects on survival pathways and neurite extension when the cortical neurons have been previously exposed to EG and these S100B effects were prevented by anti-RAGE blocking antibodies. Furthermore, nuclear factor kappa B (NF-κB) is activated by S100B in a dose- and RAGE-dependent manner and neuronal death induced by NF-κB inhibition was prevented by S100B that restored NF-κB activation levels. Together, these findings suggest that excitotoxic damage can induce RAGE expression in neurons from ischemic penumbra and demonstrate that cortical neurons respond to S100B through engagement of RAGE followed by activation of NF-κB signaling. In addition, basal NF-κB activity in neurons is crucial to modulate the extent of pro-survival or pro-death S100B effects.